2005
DOI: 10.1089/jpm.2005.8.585
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care and African Americans: Voices from the Community

Abstract: Findings suggest important clinical implications for clinicians and other health professionals. These voices from the community remind us of the heterogeneity in needs and preferences and challenge us to listen and tailor communication to each patient and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 31 publications
2
51
0
1
Order By: Relevance
“…Reasons for the observed racial differences in patterns of end-of-life care are likely complex and reflect a variety of different factors, including differences in preferences (35)(36)(37)(38), differences in the hospitals where patients are treated (39,40), differential access to care (41)(42)(43), differences in cultural, spiritual, and religious beliefs (44)(45)(46)(47), differences in education and health literacy (48), and mistrust of the medical system (49). Prior studies evaluating racial differences in patterns of end-of-life care among patients with ESRD have not described the extent to which these factors may vary geographically.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the observed racial differences in patterns of end-of-life care are likely complex and reflect a variety of different factors, including differences in preferences (35)(36)(37)(38), differences in the hospitals where patients are treated (39,40), differential access to care (41)(42)(43), differences in cultural, spiritual, and religious beliefs (44)(45)(46)(47), differences in education and health literacy (48), and mistrust of the medical system (49). Prior studies evaluating racial differences in patterns of end-of-life care among patients with ESRD have not described the extent to which these factors may vary geographically.…”
Section: Discussionmentioning
confidence: 99%
“…A few other studies have focused on the decision-making experience of racially and ethnically diverse surrogates deciding for seriously ill patients, but rather addressed their treatment preferences 7 or problems with health care provider communication. 27 The dominant theme in our analysis is the tremendous burden of decision-making surrogates experienced that transcended race/ethnicity. Surrogates reported feeling burdened in their expected role in medical, personal, and family domains.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,[22][23][24][25][26] Rare studies have considered the experience in terms of how race or ethnicity relates to surrogate decision making and then have focused on the African American perspective. 7,27 Much less is known about the decision-making experiences of Hispanic surrogates, despite the fact that Hispanics represent the fastest growing minority group among older adults in the United States. 28 The goals of this study were to describe self-reported experiences of surrogate end-of-life decision-making and to generate hypotheses about the relationship of race, ethnicity, and culture to that experience.…”
Section: Introductionmentioning
confidence: 99%
“…Content analysis as described by Strauss and Corbin (1998) was used to search the data for meaningful categories. The goal of this method is the generation of themes and concepts that emerge to describe an experience (Glaser & Strauss, 1967;Speziale & Carpenter, 2002), and has been successfully implemented in focus group data analysis (Jenkins, Lapelle, Zapka, & Kurent, 2005;Lasch et al, 2000). Focus group sessions were coded by conceptualizing underlying patterns in the data related to perceptions of risk factors, health promotion, and disease prevention behaviors related to hypertension.…”
Section: Discussionmentioning
confidence: 99%